Achievements of the ARIADNE initiative for archaeological data sharing and research - Geser, Guntram (Facultad de Filosofía y Humanidades. Museo de Antropología, 2023)
The overall objective of the ARIADNE initiative is to help the archaeological research and data management communities in Europe and beyond to more effectively share and use data, which are dispersed across many institutions and projects. The initiative developed Research Infrastructure services that enable aggregation, integration, search, and visualisation of data records which describe and link to data collections and items available in the providers’ repositories and databases. Funded under the Research Infrastructures strand of the European Union’s Framework Programme for Research and Innovation, the ARIADNE projects implemented and enhanced the ARIADNE Research Infrastructure and mobilised a growing community of institutions and collaborative projects interested to share data through the e-Infrastructure. In the ARIADNEplus project, almost 4 million data records were integrated in the ARIADNE Portal. Following a brief introduction to the ARIADNE initiative, this paper presents selected achievements of the initiative with the ARIADNEplus project. It addresses the extension and support of the ARIADNE community, the activities promoting FAIR data in archaeology, and the standardisation of datasets based on the CIDOC CRM and the domain vocabularies Getty AAT and PeriodO. It considers the ARIADNE Portal as an effective data access and research tool, and the development of Virtual Research Environments as a new innovative approach. The final remarks highlight that the ARIADNE initiative provides incentives for institutions and projects to share their data and make it useful through the ARIADNE Portal, which leverages the value of the providers’ repositories and databases. Furthermore, ways in which ARIADNE fosters cross-disciplinary fertilisation are noted, for example, between scholars and technological developers of research services.